IMPLEMENTASI PEMBELAJARAN TEMATIK DENGAN PENDEKATAN KONTEKSTUAL BERBAZIS KARAKTER RELIGIUS SEBAGAI UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SD - Fauzatul Ma’rufah Rohmanurmeta (MUADDIB Jurnal Kependidikan dan Keislaman, 2018)
Thematic learning is a learning that integrates various subjects in various themes. The low activity and learning outcomes in the students' thematic learning are thought to be caused by teachers still using conventional methods. Teachers never bring learning material into the real world. Students only understand a little about the subject matter and feel depressed when the classroom learning process takes place. This study aims to improve the activity and learning outcomes on thematic learning by using contextual approach of based on religious. The approach used in this study is a qualitative approach and is a classroom action research (PTK). Based on the results of data analysis found that the average score of student learning activities in cycle I is 12.23 and in cycle II is 15.14. While the average score of student learning outcomes in the first cycle is 61.88 and on the second cycle is 75.55. The results showed that there is an increase in activity and learning outcomes of fourth graders on integrative thematic learning with contextual approach of based on religious..